The politics of cultural retreat : imperial bureaucracy in Austrian Galicia, 1772-1867 - Vushko, Iryna (Yale University Press, 2015)
This study recounts how an international cohort of Austrian officials administered Galicia from the time of its annexation from Poland-Lithuania in 1772 up until the beginning of Polish autonomy in 1867. The author examines the interactions between these German-speaking bureaucrats and the local Galician population of Poles, Ukrainians, and Jews, and reveals how Enlightenment-inspired theories of modernity and supra-national uniformity essentially backfired, ultimately bringing about results that starkly contradicted the original intentions and ideals of the imperial governors.